Neoadjuvant Chemotherapy in Muscle-Invasive Bladder Cancer: A Nationwide Analysis of Eligibility, Utilization, and Outcomes - Nikulainen, Ilkka; Salminen, Antti P.; Högerman, Mikael; Seikkula, Heikki; Boström, Peter J.; Finnish National Cystectomy Database Research Group (MDPI AG, 2025)
Objectives: To investigate neoadjuvant chemotherapy (NAC) eligibility, utilization, and survival outcomes for muscle-invasive bladder cancer patients undergoing radical cystectomy (RC) in a Finnish population.
Materials and methods: Data from the Finnish National Cystectomy Database (2005-2017) was combined with Finnish Cancer Registry survival data. NAC utilization rates were reported, and downstaging rates were calculated based on final pathological staging. Logistic regression analyzed NAC usage and complete response (CR) predictors.
Results: Since 2011, 29% of 1157 patients received NAC. Its usage remained consistent, and the number of eligible patients not receiving NAC decreased during the study period. Among NAC patients, pathology T-category was pT0 (34%), pT1-Ta-Tis (16%), pT2 (23%), pT3 (20%), and pT4 (7%) tumors, with pN0 in 82%. In the RC + NAC group, the 5-year overall survival (OS) rates were 89% for patients with no residual disease (pT0N0), 82% for those with organ-confined residual disease (pT1, Tis, Ta, T2/N0), and 49% for patients with non-organ-confined residual disease (pT3+/N+). The corresponding cancer-specific survival (CSS) rates were 93%, 86%, and 57%, respectively. Patients with organ-confined residual disease after NAC had survival outcomes comparable to those who underwent RC alone. Higher age; odds ratio (OR) 0.93, [95% Confidence Interval (CI): 0.90-0.95] and Charlson Co-morbidity Index-score [OR 0.88 (0.79-0.98)] reduced the likelihood of receiving NAC, while a smaller center size increased the probability [OR 1.82 (1.02-3.28)]. More treatment cycles [OR 0.70, (95% CI: 0.51-0.93)] and a favorable GFR [OR 0.38 (0.16-0.88)] were associated with achieving CR.
Conclusion: We report that NAC is well-utilized across Finland, with CR rates comparable to recent trials. Additionally, our survival rates are reasonable, and even with organ-confined residual disease after NAC, survival outcomes are similar to those who underwent RC alone.